2021
DOI: 10.3389/fimmu.2021.773280
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Infiltration Analysis Demonstrates Excessive Mast Cell Activation in Psoriasis

Abstract: Psoriasis represents multiple inflammatory processes and exaggerated physiological responses to epithelial damage by innate and adaptive immune components, thus it is critical to compare the immune cell niche in disease and healthy skin. Here, we inferred the proportions of different immune cell types in psoriatic and healthy skin using the CIBERSORT algorithm with expression profiles as input. As a result, we observed a dramatic change of immune cell profiles in psoriatic skin compared with healthy skin. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…IFNγ-primed human mast cells can induce the generation of IL22-producing T H cells from CD4 + memory T cells, and this process was demonstrated in psoriasis [87]. A recent immune cell infiltrate analysis of psoriatic lesional skin revealed that receptor tyrosine kinase (c-Kit) and tryptase double-positive, activated MCs are enriched in psoriatic skin, and their number gradually decreases upon clinical treatment, supporting an important role of MC activation in the progression of psoriasis [88].…”
Section: Mast Cellsmentioning
confidence: 95%
“…IFNγ-primed human mast cells can induce the generation of IL22-producing T H cells from CD4 + memory T cells, and this process was demonstrated in psoriasis [87]. A recent immune cell infiltrate analysis of psoriatic lesional skin revealed that receptor tyrosine kinase (c-Kit) and tryptase double-positive, activated MCs are enriched in psoriatic skin, and their number gradually decreases upon clinical treatment, supporting an important role of MC activation in the progression of psoriasis [88].…”
Section: Mast Cellsmentioning
confidence: 95%
“…The immune cell proportions were determined using the CIBERSORT R package ( http://cibersort.stanford.edu/download.php ), with data from the normalized gene expression matrix of AD patients and HCs and the data from expressed reference signature genes (LM22, http://cibersort.stanford.edu/download.php ) ( Zhang et al, 2021 ). A violin plot was used to visualize the distribution of these immune cells using the “vioplot” package in R software.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, an algorithm known as cell-type identification by estimating relative subsets of RNA transcripts (CIBERSORT) has been developed for estimating numbers of immune cells ( Chen et al, 2018 ). This tool has been utilized to measure the extent of immune cell infiltration in various immune-mediated skin disorders, including psoriasis and acne vulgaris ( Yang et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of mast cells in pruritic lesions was greater than in non-pruritic lesions in psoriasis ( 84 ). Activated mast cells were more abundant in psoriatic lesions than in non-lesional psoriatic skin and in healthy subjects, whereas resting mast cells were almost entirely absent in psoriatic skin lesions ( 85 ). Importantly, the proportion of resting mast cells gradually normalized in lesional psoriatic skin during etanercept (a TNF inhibitor) therapy ( 85 ).…”
Section: Mast Cells In Psoriasismentioning
confidence: 99%
“…Activated mast cells were more abundant in psoriatic lesions than in non-lesional psoriatic skin and in healthy subjects, whereas resting mast cells were almost entirely absent in psoriatic skin lesions ( 85 ). Importantly, the proportion of resting mast cells gradually normalized in lesional psoriatic skin during etanercept (a TNF inhibitor) therapy ( 85 ). These results suggest that mast cells may be involved in the pathogenesis of psoriasis.…”
Section: Mast Cells In Psoriasismentioning
confidence: 99%